European Union Central Securities Depositories Regulation Settlement Discipline Regime impact on buy-side bond market participants - Mežrozis, Kārlis (Riga Graduate School of Law, 2022)
The Covid-19 pandemic gave rise to unprecedented challenges for the European economy. It highlighted the need for a more flexible, efficient, and reliable financial system that could effectively alleviate the immense financial pressures on Europe’s economy. Thus, more attention was given to the development of Europe’s Capital Markets Union. As part of the development process, an important piece of legislation came into force on February 2, 2022 – namely the Settlement Discipline Regime from the Central Securities Depositories Regulation. This piece of legislation aims to improve and unify the post-trading processes across the entire financial markets of Europe. Market participants indicated that they do not fully support the requirements set out in the regulation and thus a question arose about how the CSDR aims to achieve settlement discipline in the financial markets and what could be the effects of this regulation on financial markets and its participants. Therefore, this thesis discusses and examines the potential impacts of the CSDR on bond markets and buy-side bond market participants. Considering legal, technical, administrative, and financial aspects of implementing changes to fully comply with the regulatory requirements.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Financial markets; Central Securities Depositories Regulation